The Rule of Law in Poland – Values and Legalism - Faber-Wiercińska, Anna (Reversed Rule of Law in the Creation, Interpretation and Application of Law in Poland: Methods and Consequences, 2026)
The rule of law is one of the fundamental principles of a state’s political system; however, in practice, its meaning proves to be non-uniform. The concept is generally understood as a set of principles and values that constitute the legal order of the state. This Chapter explores the understanding of the rule-of-law clause within the Polish legal system. It first presents the historical background to the introduction ofthis clause, which entered the Polish legal order through the December Amendment to the Constitution of the People’s Republic of Poland in December 1989, serving primarily a symbolic function. It then outlines the definition of the rule of law coined by Polish legal scholars, who view the concept as encompassing systemic principles, fundamental rights and freedoms, and principles of good legislation. Further, the Chapter examines how this clause has been interpreted in the jurisprudence of the Constitutional Tribunal, and the role it has played in shaping the state’s system. For the CT, the clause served as a source of systemic principles and individual rights and freedoms before the current Constitution came into force. Today, it is primarily interpreted as a source of the principles of good legislation. Keywords: Art. 2, Constitutional Tribunal, December Amendment, democracy, legalism, rule of law